Stabilization of the First-Order Phase Transition Character and Enhancement of the Electrocaloric Effect by Na0.5bi0.5< Substitution in Batio3 Ceramics - Karakaya, Merve; Karakaya, Merve; Adem, Umut; Gurbuz, Irem; Fulanovic, Lovro; Adem, Umut (Royal Soc Chemistry, 2024)
The electrocaloric properties of BaTiO3-based Pb-free ferroelectric materials are widely investigated. One approach to achieving a large electrocaloric response is making use of the substantial polarization change associated with the first-order phase transition at the Curie temperature. To make use of this approach, we have investigated the electrocaloric response of (1 - x)BaTiO3-xNa0.5Bi0.5TiO3 (BT-NBT) ceramics for x = 0.05, 0.10, 0.20 and 0.30. For this BT-rich part of the solid solution, it is established that increasing the NBT content increases the tetragonality of the BaTiO3. We show that this increase in tetragonality with NBT substitution helps to maintain the first-order nature of the phase transition in BaTiO3 and correspondingly a large electrocaloric response, despite the simultaneous enhancement of relaxor ferroelectric character with the NBT substitution. A significantly larger effective electrocaloric temperature change (Delta Teff) of 1.65 K was obtained for the x = 0.20 sample under 40 kV cm-1, using the direct measurement of the electrocaloric effect, which is in reasonable agreement with the indirect measurements.
Fulanovic, Lovro/0000-0002-9194-5688; Gurbuz, Irem/0000-0002-4419-1000
Keywords: [No Keyword Available]